FACTORS THAT INFLUENCE GOING CONCERN AUDIT OPINION ACCEPTANCE (TEXTILE AND GARMENT SUBSECTOR 2020-2022) - Hartina, Marini; Daryatno, Andreas Bambang (Graduate Program of Universitas Tarumanagara, 2025)
An auditor's going concern opinion, which pertains to an entity's ability to continue as is, is a wonderful thing that calls for competent judgment. This study aims to determine the effects of financial distress, operating cash flow, previous year audit opinion, and company growth on going concern opinion acceptance on the manufactured-consumer goods sector, which is a subsector of textile and garment companies listed on the Indonesia Stock Exchange, either partially or simultaneously, for the 2020-2022 period. Purposive sampling is being used in this study to identify which companies will serve as observation samples, and documentation will be used as the observation method. Binary logistic regression is the analysis method. According to the findings, all independent variables have no effect on opinion acceptance in part. Concurrently, every independent variable. Research Implications, Companies that are similar or not, can continue to make efforts to control and good strategies in maintaining their business continuity in order to continue to survive and gain a competitive advantage in the industry with the Company's best ability in order to achieve Company goals. This is not easy to do, but the Company can continue to evaluate performance and innovations that adjust to the times and customer interests. The current audit approach is already risk-based (risk-based audit) and business continuity, so that auditors will continue to see how a company's performance in maintaining its business continuity, internal control, to assess the risks that will arise in the audit process, obtain sufficient and appropriate audit evidence, which ultimately wants to obtain sufficient confidence in the fairness of the financial statements to draw conclusions in the preparation of an independent auditor's report (audit opinion).